2004
DOI: 10.1073/pnas.0405695101
|View full text |Cite
|
Sign up to set email alerts
|

L-SIGN (CD209L) and DC-SIGN (CD209) mediate transinfection of liver cells by hepatitis C virus

Abstract: Target cell tropism of enveloped viruses is regulated by interactions between viral and cellular factors during transmission, dissemination, and replication within the host. Binding of viral envelope glycoproteins to specific cell-surface receptors determines susceptibility to viral entry. However, a number of cell-surface molecules bind viral envelope glycoproteins without mediating entry. Instead, they serve as capture receptors that disseminate viral particles to target organs or susceptible cells. We and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(174 citation statements)
references
References 70 publications
7
165
0
2
Order By: Relevance
“…L-SIGN is able to bind and permit entry into the cell of HIV (4,5), hepatitis C virus (HCV) (10), Ebola virus (11), severe acute respiratory syndrome (SARS) virus (12), CMV (13), and Sindbis virus (14). Current data support the idea that the interaction allows HIV and HCV to be transmitted in trans to other cells, e.g., T cells and hepatocytes (4,5,15), whereas it is thought to result in direct infection by other viruses, e.g., Ebola and SARS (12,16). Recently, L-SIGN has also been shown to serve as a receptor for bacterial pathogens, e.g., Mycobacterium tuberculosis (17) and parasites such as Schistosoma mansoni (18).…”
Section: Endritic Cell (Dc)mentioning
confidence: 95%
“…L-SIGN is able to bind and permit entry into the cell of HIV (4,5), hepatitis C virus (HCV) (10), Ebola virus (11), severe acute respiratory syndrome (SARS) virus (12), CMV (13), and Sindbis virus (14). Current data support the idea that the interaction allows HIV and HCV to be transmitted in trans to other cells, e.g., T cells and hepatocytes (4,5,15), whereas it is thought to result in direct infection by other viruses, e.g., Ebola and SARS (12,16). Recently, L-SIGN has also been shown to serve as a receptor for bacterial pathogens, e.g., Mycobacterium tuberculosis (17) and parasites such as Schistosoma mansoni (18).…”
Section: Endritic Cell (Dc)mentioning
confidence: 95%
“…Liver/lymph nodespecific intercellular adhesion molecule-3-grabbing integrin (L-SIGN) is a calcium-dependent lectin expressed mainly on endothelial cells of liver and lymph nodes (Koppel et al, 2005). Jason et al have demonstrated that L-SIGN is a liver-specific receptor for HCV, and may play important roles in HCV infection and immunity (Gardner et al, 2003;Cormier et al, 2004). L-SIGN may establish cellular interactions with T cells (Bashirova et al, 2001) and enable activated T cells to recirculate to the liver or to the lymph nodes through interactions with L-SIGN (Cocquerel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…L-SIGN may establish cellular interactions with T cells (Bashirova et al, 2001) and enable activated T cells to recirculate to the liver or to the lymph nodes through interactions with L-SIGN (Cocquerel et al, 2006). L-SIGN and DC-SIGN may rather contribute to the establishment or persistence of infection, both by the capture and delivery of HCV to the liver and by modulating dendritic-cell functions as suggested by Cormier et al (2004) and Lozach et al (2004). CHST4 (Carbohydrate sulfotransferase) encodes an N-acetylglucosamine 6-O sulfotransferase.…”
Section: Discussionmentioning
confidence: 99%
“…Because neither molecule is expressed on hepatocytes, they are unlikely to function as direct entry receptors. DC-SIGN-and L-SIGN-bound HCVpp can, however, be transferred to susceptible cells in co-culture, suggesting that these molecules may aid infection in vivo by capturing virions for transmission to hepatocytes (64,65).…”
Section: Interaction With Cell-surface Factorsmentioning
confidence: 99%